Concurrent management of nasal bone expansion from nasal polyposis (Woakes' disease). Issue 5 (9th August 2022) - Dickie, Alexander; Rotenberg, Brian; Sowerby, Leigh
Abstract: Background: Woakes' disease is the eponymous name for severe chronic rhinosinusitis with nasal polyposis (CRSwNP) leading to thinning and expansion of the nasal pyramid. The endoscopic treatment of the sinus disease, while extensive, is standard practice for the rhinologist. Management of their external nasal deformities, for many, is not. Simultaneous closed rhinoplasty in these patients is straightforward, easy to perform and achieves an excellent esthetic outcome. Methods: Three patients with CRSwNP and notable nasal pyramid expansion are reviewed. All patients had eosinophilic disease, with two having NSAID‐exacerbated respiratory disease (N‐ERD). All three patients underwent full house endoscopic sinus surgery from May 2018 to September 2019 along with simultaneous closed rhinoplasty. Two of these patients required only external digital pressure to fracture the nasal bones for gentle Boies elevator repositioning, while the third had osteotomies with minimal force to aid reduction. Results: Postoperatively, patients had excellent nasal airway symptom improvement, and the cosmetic results following rhinoplasty demonstrated normalization of symmetry, profile, and contour of the nose with high‐patient satisfaction. Conclusion: Based on our experience, simultaneous rhinoplasty on the thinned nasal bones of Woakes' Disease patients is not only easy to perform, but provides excellent cosmetic and functional results by allowing bone to remodel in the appropriate position, and avoids a second‐stage rhinoplasty.